National Health Interview Survey, 1996: Access to Care Supplement ([Verlag nicht ermittelbar], 1999)
The purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. This supplement includes variables from the NHIS core Person File (see NATIONAL HEALTH INTERVIEW SURVEY, 1996 [ICPSR 2661]), including sex, age, race, marital status, veteran status, education, income, industry and occupation codes, and limits on activity. The 1996 Access to Care questionnaire was administered throughout the full year with the exception of the last three weeks of December. Variables included in the data file cover estimated number of doctor visits in the past 12 months, estimated short-stay hospital episode days in the past 12 months, usual person/facility used for medical care, type of doctor seen, type of facility, availability of referrals, and reason for not using the facility currently. Also included were items concerning the main reason for no usual source of care, whether cost was a reason for not seeking care, and the need for dental care, prescription medicines, eyeglasses, and mental health care.